Challenging the placeless imaginary in digital memories: The performation of place in the work of Forensic Architecture. (June 2021) - Mandolessi, Silvana
This article discusses the imaginary that digital memories are 'placeless', which refers to the notion that, among the changes that memory has experienced under the impact of digital media, one is the loss of a significant link to place. I contend that digital memories are not placeless memories, but, on the contrary, that place is central for digital memory work. Drawing on the concept of 'performation', I seek to demonstrate how place is created, executed and staged in the digital ecology. To illustrate this, I analyse two works of the research agency Forensic Architecture, 'Hannibal in Rafah' and 'Saydnaya: Inside A Syrian Torture Prison', in which 'place' plays a central role in the shaping of digital memory. Digital media's 'inherently archival' nature acquires a different meaning in these works: it is the process of collecting and mapping the dispersed fragments of data that transforms the archive into memory.